2014
DOI: 10.1182/blood-2013-10-535856
|View full text |Cite
|
Sign up to set email alerts
|

Green neutrophilic inclusions could be a sign of impending death!

Abstract: A n 88-year-old African American man was evaluated for altered mental status and was found to have a urinary tract infection. He developed septic shock with a positive blood culture for Escherichia coli, confirmed as extended spectrum beta-lactamase. During the course of infection, the aspartate aminotransferase and alanine aminotransferase increased rapidly from 50 U/L and 22 U/L to 348 U/L and 116 U/L, respectively. The bilirubin increased from 3.4 mg/dL to 4.4 mg/dL (direct: 3.2 mg/dL) with increased intern… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
16
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 0 publications
3
16
0
Order By: Relevance
“…They can be seen in both neutrophils and monocytes. These inclusions are associated with a high mortality rate, but we show that their appearance is not always fatal, as suggested in previous reports (Harris et al , ; Jazaerly & Gabali, ). Because of their strong association with death and critical illness, we suggest they be described as ‘critical green inclusions’.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…They can be seen in both neutrophils and monocytes. These inclusions are associated with a high mortality rate, but we show that their appearance is not always fatal, as suggested in previous reports (Harris et al , ; Jazaerly & Gabali, ). Because of their strong association with death and critical illness, we suggest they be described as ‘critical green inclusions’.…”
Section: Discussionsupporting
confidence: 90%
“…In the three reported cases, death occurred within 2 d of recognition of the inclusions (Harris et al , ; Jazaerly & Gabali, ). Disease associations with green neutrophil inclusions included acute liver failure secondary to acetaminophin overdose, lactic acidosis with multisystem organ failure subsequent to trauma (Harris et al , ) and Escherichia coli ‐associated septic shock (Jazaerly & Gabali, ). Harris et al () suggested that the inclusions were related to blood‐borne bile products.…”
mentioning
confidence: 98%
“…In the past decade, nine publications encompassing 70 cases have reported green cytoplasmic inclusions in neutrophils and occasionally in monocytes in patients suffering from acute liver damage. [1][2][3][4][5][6][7][8][9] The presence of these cytoplasmic deposits within the neutrophils is most probably due to a lipofuscin-like substance released from necrotic liver parenchymal cells and taken up by phagocytosis. 3,7 Biological findings described in these patients are as follows: (a) elevated liver transaminases associated with acute liver tissue damage, (b) elevated lactate dehydrogenase (LDH) levels probably secondary to hepatic necrosis, and (c) elevated lactate values, seen as a predictor of survival.…”
Section: Dear Editorsmentioning
confidence: 99%
“…3,4 The second case showed a much higher percentage of inclusion-filled neutrophils (peak at 18%) in accordance with the first described cases. 1,2 Other studies refer to multiple or incidental neutrophils with green inclusions. [5][6][7][8] It is reasonable to think that the higher the number of neutrophils with inclusions, the more extensive the tissue damage, as more lipofuscin-like substance is released from the necrotic tissue and taken up by neutrophils.…”
Section: Dear Editorsmentioning
confidence: 99%
“…The earliest published cases include anecdotal reports from patients with a wide variety of comorbid conditions and associated liver dysfunction [1,2,3,4,5]. Subsequent reports emphasized that such inclusions are associated with impending death and a high rate of mortality [6,7,8]. In the most comprehensive study to date, Hodgson et al [7 ]described 20 such patients including the first nonfatal cases, and also reported biochemical findings suggesting that the inclusions are comprised of a lipid-rich, lipofuscin-like material or lysosomal degradation product(s) that may be released from necrotic hepatocytes.…”
Section: Tablementioning
confidence: 99%